Trends in Checkpoint Inhibitor Therapy for Advanced Urothelial Cell Carcinoma at the End of Life: Insights from Real‐World Practice. (3rd April 2019) - Parikh, Ravi B.; Galsky, Matthew D.; Gyawali, Bishal; Riaz, Fauzia; Kaufmann, Tara L.; Cohen, Aaron B.; Adamson, Blythe J.S.; Gross, Cary P.; Meropol, Neal J.; Mamtani, Ronac
Abstract: Several immune checkpoint inhibitor therapies (CPIs) have been approved to treat metastatic urothelial cell carcinoma (mUC). Because of the favorable toxicity profile of CPI compared with chemotherapy, oncologists may have a low threshold to prescribe CPI to patients near the end of life. We evaluated trends in initiation of end‐of‐life systemic therapy in 1, 637 individuals in the Flatiron Health Database who were diagnosed with mUC between 2015 and 2017 and who died. Rates of systemic therapy initiation in the last 30 and 60 days of life were 17.0% and 29.8%, respectively. The quarterly proportion of patients who initiated CPI within 60 days of death increased from 1.0% to 23% during the study period ( p trend < .001). After CPI approval, end‐of‐life CPI initiation significantly increased among patients with poor performance status ( p trend = .020) and did not significantly change among individuals with good performance status. The quarterly proportion of patients who initiated any systemic therapy at the end of life doubled (17.4% to 34.8%) during the study period, largely explained by increased CPI use. These findings suggest a dramatic rise in CPI use at the end of life in patients with mUC, a finding that may have important guideline and policy implications. Abstract : Because immune checkpoint inhibitor therapies (CPI) lack the toxicities of chemotherapy, oncologists may prescribe CPI to patients at the end of life. This article describes real‐world patterns of CPI initiation near the end of life among individuals with metastatic urothelial cell carcinoma.